2015
DOI: 10.1080/10538712.2015.1006749
|View full text |Cite
|
Sign up to set email alerts
|

The NICHD Investigative Interview Protocol: A Meta-Analytic Review

Abstract: Systematic review and meta-analysis of literature were conducted examining the effectiveness of the National Institute for Child Health and Human Development Investigative Interview Protocol in improving the quality of child forensic interviews. Online databases were searched for journal articles published between the years 2000 and 2013. Measures of interview quality were the type of interviewer utterances and the amount of information provided by children. Five studies met criteria for inclusion in the meta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 25 publications
5
27
0
1
Order By: Relevance
“…Previous studies compared no protocol interviews with NICHD Protocol interviews from the same interviewers (see Benia et al, ; Cyr & Lamb, ; Lamb et al, in press; Lamb et al, 2009; Orbach et al, ; Sternberg, Lamb, Davies, & Westcott, ). These studies have shown that the NICHD interviews contain more invitations/open prompts and fewer directives, option‐posing, and suggestive questions than no protocol interviews.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies compared no protocol interviews with NICHD Protocol interviews from the same interviewers (see Benia et al, ; Cyr & Lamb, ; Lamb et al, in press; Lamb et al, 2009; Orbach et al, ; Sternberg, Lamb, Davies, & Westcott, ). These studies have shown that the NICHD interviews contain more invitations/open prompts and fewer directives, option‐posing, and suggestive questions than no protocol interviews.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on rapport building and asking open‐ended prompts has also been a core theme in a widely used interview protocol, which has received considerable scientific support. This protocol is called the National Institute of Child Health and Human Development Protocol (NICHD Protocol; Benia, Hauck‐Filho, Dillenburg, & Stein, ; Lamb, Orbach, Hershkowitz, Esplin, & Horowitz, ).…”
Section: Children's Memorymentioning
confidence: 99%
“…Similar to other national surveys, APSAC and the CornerHouse/Finding Words/RATAC combined protocols were the next most popular training methods reported by our sample. Although the NICHD protocol is the most widely researched and validated (Benia et al, ), only 13.6% of interviewers reported receiving training in this protocol. This finding is similar to levels of NICHD protocol use reported in previous surveys (e.g., 10%; MRCAC, ).…”
Section: Discussionmentioning
confidence: 99%
“…The NCA recognizes a number of national and state interviewing models as “competency‐based” and thus sufficient for accreditation purposes (see NCA, ). Among the most extensively researched is the National Institute of Child Health and Human Development's (NICHD) Protocol, which consistently elicits more detailed child responses with higher‐quality interview questions than more traditional methods in both laboratory and field studies (see Benia, Hauk‐Filho, Dillenberg, & Stein, ; Cyr & Lamb, ; Lamb et al, ; Orbach, Hershkowitz, Lamb, Esplin, & Horowitz, ; Sternberg, Lamb, Orbach, Esplin, & Mitchell, ; and for a detailed description of this protocol, see Lamb, Orbach, Hershkowitz, Esplin, & Horowitz, ). The U.S. Department of Justice recently produced a bulletin “Child Forensic Interviewing: Best Practice Guidelines”, which incorporated generally accepted best practices from the NICHD and several other major forensic interviewer training programs: the National Children's Advocacy Center (NCAC), the American Professional Society for the Abuse of Children (APSAC), the CornerHouse Interagency Child Abuse Evaluation and Training Center, and the Gunderson National Child Protection Training Center (Newlin et al, ).…”
Section: Current Forensic Interview Protocolsmentioning
confidence: 99%
“…How many directives that are needed depends on the initial disclosure in the interview and age and personality of the child. Younger children give shorter disclosures than older children (Benia, Hauck‐Filho, Dillenburg, & Milnitsky Stein, ; Hershkowitz, Lamb, Orbach, Katz, & Horowitz, ). Another example is that children with autism spectrum disorder have difficulties in freely recalling information and need more cues to recall (directives; Almeida, Lamb, & Weisblatt, ; Maras, Gaigg, & Bowler, ).…”
Section: Definition Of Qualitymentioning
confidence: 99%